Interactive language teaching - Rivers, Wilga M. (Cambridge [Cambridgeshire] : New York : Cambridge University Press, 1987)
Teachers and writers describe the approaches and techniques they have incorporated into their own teaching.
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching; Social interaction